Informed choice in genetic screening for thalassaemia during pregnancy: audit from a national confidential inquiry. Issue 7231 (5th February 2000) - Modell, Bernadette; Harris, Rodney; Lane, Beverley; Khan, Maren; Darlison, Matthew; Petrou, Mary; Old, John; Layton, Mark; Varnavides, Lysandros
Abstract: Objective: National audit of informed choice in antenatal screening for thalassaemia. Design: Audit from the UK Confidential Enquiry into Counselling for Genetic Disorders. Setting: Thalassaemia module of the UK Confidential Enquiry into Counselling for Genetic Disorders. Subjects: 138 of 156 couples who had had a pregnancy affected by a major β thalassaemia from 1990 to 1994. Main outcome measures: How and when genetic risk was identified for each couple, and whether and when prenatal diagnosis was offered. Results: Risk was detected by screening before or during the first pregnancy in 49% (68/138) of couples and by diagnosis of an affected child in 28% (38/138) of couples. Prenatal diagnosis was offered in 69% (274/400) of pregnancies, ranging from 94% (122/130) for British Cypriots to 54% (80/149) for British Pakistanis and from 90% in the south east of England to 39% in the West Midlands. Uptake of prenatal diagnosis was 80% (216/274), ranging from 98% (117/120) among British Cypriots in either the first or second trimester to 73% (35/48) among British Pakistanis in the first trimester and 39% (11/28) in the second trimester. A demonstrable service failure occurred in 28% (110/400) of pregnancies, including 110 of 126 where prenatal diagnosis was not offered and 48 of 93 that ended with an affected liveborn infant. Conclusion: Although antenatal screening and counselling for haemoglobin disorders are standard practices in the United Kingdom, they are delivered inadequately and inequitably. An explicit national policy is needed, aiming to make prenatal diagnosis in the first trimester available to all couples and including ongoing national audit.